Organizational characteristics fostering intellectual capital in Canada and the Middle East - Manassian, Armond (2009)
Purpose – This study sets out to examine how organizational characteristics are related to intellectual capital and how these variables are different between Canadian and Middle East contexts. Design/methodology/approach – A questionnaire was developed to measure the four major study constructs, i.e. intellectual capital, culture, climate, and organizational traits. Each of these constructs was represented by a number of subscales that were subjected to ANOVA and correlations to test the hypotheses. Findings – The analysis showed that all three categories of characteristics (culture, climate, and other traits) are significantly correlated with IC management. The results also indicated significant differences in all organizational characteristics and IC management between Canada and the Middle East. Research limitations/implications – Culture, climate, and other traits are important enablers for the effective management of IC. Although the research tested three culture variables, four climate variables, and two other traits, future research should investigate these variables and the interactions among them more thoroughly. Practical implications – The results have implications for organizations operating in different international contexts. Managers can use the results for more effective and efficient management of organizational characteristics that would foster IC management. Originality/value – The research provides a comprehensive study of enablers of effective IC management, an area of study that has not received much attention in the past. It also provides insight as to why effective IC management may be more successful in certain countries.